Digital Environment Learning (DEL): Creativity in Framework of Digital Literacy - Rudyanto, Hendra Erik; Pradana, Lingga Nico; Mumtahana, Hani Atun; Pamungkas, Ridho (Profesi Pendidikan Dasar, 2023)
The surge in digital literacy emerged as a prominent trend during the era of online learning in elementary schools. However, the success of connecting the digital environment to the learning process is contingent upon the teacher's proficiency. Consequently, we introduced DEL (Digital Enhanced Learning), an instructional approach that fully integrates digital technology into all learning devices. This study seeks to assess students' digital literacy and creativity during DEL activities in elementary schools conducted over a period of 10 weeks. A total of 290 students participated in the DEL activities. Students' digital literacy and creativity were evaluated using two instruments: DELQ (Digital Enhanced Learning Questionnaire) and CET (Creativity Evaluation Tool). DELQ gauged students' digital literacy, while CET assessed creativity. ANOVA was employed for data analysis to evaluate the consistency and achievement of students. The findings of this study indicate that DEL activities contribute to enhanced creativity, specifically in the aspects of fluency and elaboration. Students' digital literacy plays a pivotal role in supporting the fluency and elaboration processes during learning activities. Moreover, the effectiveness of DEL activities, as perceived through students' digital literacy, indicates an improvement in knowledge related to digital literacy. In summary, this study underscores the positive impact of digital-based activities in fostering both digital literacy and creativity among elementary school students